Overlapping sphincteroplasty: is it the standard of care? - Goetz, Laura H; Lowry, Ann C (Clinics in colon and rectal surgery, 2005)
Anal sphincter injury secondary to obstetric trauma during vaginal delivery occurs in nearly one of every five women. Episiotomy, forceps delivery, and prolonged second stage of labor have all been shown to increase the risk of sphincter disruption. One third of these women will go on to have alterations in anal continence ranging from occasional incontinence to gas to severely debilitating incontinence to solid stool. Symptoms often arise many years after delivery, suggesting that factors such as nerve damage and progressive degeneration of muscle fibers contribute to incontinence. Surgical treatment of fecal incontinence secondary to sphincter injury has been varied and creative attempts have been made to find the repair with the greatest durability and fewest complications. Over the past few decades, overlapping sphincteroplasty emerged as such a repair with many reports of excellent short-term outcomes. Recently, however, published reports of long-term data reveal decreased function over time, causing many to question whether this repair truly is the best possible treatment. Several controversies have arisen. These include (1) optimum timing from injury to repair; (2) how best to perform the repair; (3) whether or not fecal diversion, either medical or surgical, is beneficial; (4) whether or not pudendal neuropathy predicts outcome; and finally, (5) if patient's age at the time of repair affects outcome. Randomized controlled trials are lacking, so any conclusions drawn from reviewing current literature must be evaluated with this in mind. Nonetheless, important information can be gleaned from the available literature and future studies designed with the hope of improving treatment for this life-altering condition.